Synthesis, crystal structures, phase transition characterization and thermal properties of the (1-x)PbZrO3-xPb(Co1/3Nb 2/3)O3 solid solution system - W. Banlue (2018)
The phase transition behavior of the (1-x) PbZrO3-xPb(Co 1/3Nb2/3)O3 (PZCN) solid solution system (0 ≤ x ≤ 0.30) has been investigated by X-ray diffraction and DSC. In the solid solution, for x ≤ 0.20, the transition shows a first-order phase transition behavior and its antiferroelectric (AFE) crystal structure is orthorhombic. The transition temperature gradually decreases with increased Co2+/Nb5+ concentration. On the composition range 0.20 ≤x≤ 0.30, a typical relaxor-like behavior is displayed. The low temperature crystal structure is pseudo-cubic in this composition range. With these data, the ferroelectric phase diagram between PZ and PCoN has been established. © 2008 Trans Tech Publications, Switzerland.